HUBUNGAN ANTARA KECERDASAN EMOSI DENGAN CARA BELAJAR PESERTA DIDIK DI SMA NEGERI 2 LENGAYANG KABUPATEN PESISIR SELATAN - Nisa, Khairun; Kasih, Fitria; Nofrita, Nofrita (Bimbingan dan Konseling, 2014)
The emotional intelligence is one of the supporting factors in the learning process of school. The purpose of the research are: (1) description of the emotional intelligence of students, (2) Description of how learnersâ learning, (3) The relationship between emotional intelligence and the way students learn. This research using quantitative descriptive correlational approach. In the entire study population of learners SMAN 2 Lengayang South Coastal District, amounting to 685 people. Sampling using stratified ramdom sampling technique. The total sample of 85 people. Data collection tools such as questionnaires. Emotional intelligence to analyze data in a way students learn using percentage analysis techniques, while hypothesis testing to see the relationship of emotional intelligence by learning if learners using correlation techniques. The results of the research of the students at SMAN 2 Lengayang South Coastal District has the emotional intelligence intelligent quite good as are ways of learning and the relationshop of emotional intelligence by learning rhitung of 0.479> of rtabel df of 0.2133 At 84 with the significant level of 0.000<0.05. So the relationship between emotional intelligence and the way students learn at SMAN 2 Lengayang South Coastal District is located at the level of the relationship is strong enough.